Debridement, antibiotics, and implant retention after revision arthroplasty: antibiotic mismatch, timing, and repeated DAIR associated with poor outcome. (1st April 2022) - Veerman, Karin; Raessens, Joris; Telgt, Denise; Smulders, Katrijn; Goosen, Jon H. M.
Abstract : Aims: Debridement, antibiotics, and implant retention (DAIR) is a widely accepted form of surgical treatment for patients with an early periprosthetic joint infection (PJI) after primary arthroplasty. The outcome of DAIR after revision arthroplasty, however, has not been reported. The aim of this study was to report the success rate of DAIR after revision arthroplasty with a follow-up of two years. Methods: This retrospective study, conducted at the Sint Maartenskliniek, Nijmegen, the Netherlands, included 88 patients who underwent DAIR within 90 days of revision total hip or total knee arthroplasty between 2012 and 2019. Details of the surgical procedures and PJI were collected. Univariate analysis and a subgroup analysis of the culture-positive group were performed. Kaplan-Meier survivorship curves were constructed. Results: The overall success rate of DAIR, with respect to the retention of components and the cure of infection, was 68% after two years. DAIR performed with an interval of > 30 days after the index revision procedure (odds ratio (OR) 0.24 (95% confidence interval (CI) 0.08 to 0.72); p = 0.008), a repeated DAIR within 90 days (OR 0.37 (95% CI 0.14 to 0.97); p = 0.040), and the use of an immunosuppressive agent (OR 0.13 (95% CI 0.02 to 0.67); p = 0.012) were associated with a significantly reduced success rate. In the culture-positive group, a mismatch between the antibiotic treatment and the susceptibility of the organism was associated with a significantly lower success rate (OR 0.13 (95% CI 0.03 to 0.62); p = 0.007). Conclusion: DAIR is an acceptable form of surgical treatment for patients with a suspected early PJI after revision arthroplasty of the hip or knee. DAIRs performed after a prolonged interval, multiple DAIRs, and antibiotic mismatches were significantly associated with an increased risk of failure. Optimization of the host immune response and the prevention of antibiotic mismatch are modifiable factors that may improve the outcome. The high rate of mismatches was an important finding, underlining the need for a review of the local microbiological data, which might improve the outcome. Cite this article: Bone Joint J  2022;104-B(4):464–471.